Determinants of green product purchase decisions - Achmad Tarmizi; Muhamad Al Faruq Abdullah (Sean Institute, 2024)
This research aims to determine the positive influence of environmental awareness, knowledge, and price on purchasing decisions for environmentally friendly products. Data collection in this research was carried out using a survey method by distributing 100 questionnaires using accidental sampling. The accidental sampling technique draws a sample size if the exact population size is unknown and yet to be discovered and uses multiple regression analysis with the SPSS version 26 program as a tool for processing and analyzing research results. The research results show that the Environmental Awareness variable does not significantly influence purchasing environmentally friendly products. The knowledge variable substantially influences the decision to purchase environmentally friendly products. The price variable substantially affects the decision to purchase environmentally friendly products. The environmental awareness, knowledge, and price variables greatly influence the decision to purchase environmentally friendly products.